Tailoring Sexual Health Interventions for Middle-Aged and Older Adults, Including Vulnerable Populations: A Scoping Review. Issue 4 (2nd October 2022) - Tyndall, Ian; Hartland, Tess; Banerjee, Moitree; Giacomelli, Victoria; Ball, Isabelle; Churchill, Susan; Pereira, Antonina; Lowry, Ruth
Abstract: Objective: This scoping review aims to synthesize existing literature on good practice in sexual health interventions for adults over 45 years and in vulnerable groups. Methods: Using PRISMA-ScR guidelines, search terms focused on sexual health, good practice, and vulnerable groups, in over-45s. Results: Of the nine studies that met the inclusion criteria, seven were focused on HIV and risk reduction. Use of alternative methods of communication, alongside inclusion of behavioral and cognitive measures such as condom use and perceived stigma, was key to tailoring interventions. Conclusions: This review highlights the imperative for further research on sexual health interventions with these overlooked populations.